Choice of the angler: Estimating single-site recreation demand using revealed preference data. (December 2016) - Wallentin, Erik
The author proposes a novel application for estimating demand for a single recreation site when data are limited. An aggregated zonal travel cost model is outlined and estimated in a panel setting using a negative binomial estimator with time-specific constants to capture unobserved time-varying quality attributes. The data are based on catch records for the Mörrum river salmon fishery, one of the most popular sport fishing destinations in Northern Europe. These are aggregated to the municipal level for the zonal estimation and give number of visits per municipality per week for the period 1999–2011. The results confirm the expected negative influence of travel cost on visits. Further, the inclusion of time-specific constants does not render all time-varying quality attributes insignificant.